Physicochemical Characteristics and Microbiological Quality of Honey Produced in Benin - AGBANGNAN DOSSA, COKOU PASCAL (My University, 2018)
Honey is a very complex biological product. It has great diversity, giving it a multitude of properties, both nutritionally and therapeutically. This study aimed to study the physicochemical and microbiological characteristics of honeys collected during the dry and rainy seasons in the different phytogeographical areas of Benin. The study revealed that all honeys had pH, water content, electrical conductivity, ash content, free acidity, total sugars, and reducing sugars, respectively, ranging within 3.65–4.09; 12.07–13.16%; 530.25–698.50 ????s/cm; 0.42–0.53%; 35.67–40.52meq/kg; 60–70%; and 58–70%. Moisture content, total sugars, and reducing sugars varied very significantly (???? < 0.05 to ???? < 0.001) from one area to another and from one season to another. However, only the production season has a significant influence (???? < 0.05) on the pHof the honey. With regard to the ash content, free acidity, and electrical conduction, no significant difference (???? > 0.05) between the zones or between the seasons was observed. The results of the microbiological characterization showed that there is heterogeneity in the microbial load. These results have shown that these honeys meet international standards and their characterization will make it possible to obtain Beninese quality labels.